Bifurcation Configuration Is an Independent Risk Factor for Aneurysm Rupture Irrespective of Location - Liu, Qinglin; Jiang, Peng; Jiang, Yuhua; Li, Shaolin; Ge, Huijian; Jin, Hengwei; Li, Youxiang (Frontiers in Neurology, 2019)
Background: Bifurcation and sidewall aneurysms have different rupture risks, but whether this difference comes from the location of the aneurysm is not clear. The objective of this study is to illustrate the rationality of ranking bifurcation configuration as an independent risk factor for aneurysm rupture. Methods: Morphological features of 719 (216 ruptured) aneurysms were automatically extracted from a consecutive cohort of patients via PyRadiomics. Rupture risks and morphological features were compared between bifurcation and sidewall aneurysms, and lasso regression was applied to explore the morphological determinants for rupture in bifurcation and sidewall aneurysms. Rupture risks and morphological features of bifurcation aneurysms in different locations were analyzed. Multivariate regression was performed to explore the risk factors for aneurysm rupture. Results: Twelve morphological features were automatically extracted from PyRadiomics implemented in Python. The rupture risks was higher in bifurcation aneurysms (P<0.01), and morphological features Elongation and Flatness were much lower in ruptured bifurcation than sidewall aneurysms (P=0.036, 0.011, respectively). Elongation and Flatness were the morphological determinants for rupture in bifurcation aneurysms, whereas Elongation and SphericalDisproportion were determinants for sidewall aneurysms. Different rupture risks and morphological features were found between sidewall and bifurcation aneurysms of the same location, and among bifurcation aneurysms of different locations. In multivariate regression, bifurcation configuration was an independent risk factor for aneurysm rupture (OR 3.007, 95% CI 1.752-5.248, P<0.001).Conclusions: Bifurcation configuration is an independent risk factor for aneurysm rupture irrespective of location.